The Relationship between the Sexual Abstinence Period and Sperm Parameters in Normozoospermia Infertile Men - Salman, Muhammad Khalil; Mohsen, Aqeel Adel; obiad, Jihad Shanan Fayyad; Al-Rubaie, Dalya Hakim Saeed Rahim (American Journal of Biology and Natural Sciences, 2024)
Background: According to WHO guidelines, the abstinence period for semen analysis ranges from 2 to 7 days. The current study aimed to study the relationship between the abstinence period and semen parameters represented by the concentration of the sperm, the progressive movement of the sperm, the normal shape of the sperm, and the volume of semen in Normozoospermia patients. Methods: The study was conducted in the laboratories of the Fertility Center of Al-Sadr Teaching Hospital in Al-Najaf Governorate - Iraq. The age of the patients ranged from 20 to 44 and the marriage period ranged from 1 to 8 years. The results of the semen analysis of the samples were recorded and a group of normozoospermia was determined based on the World Health Organization’s guideline. The relationship between the abstinence period and the parameters of semen represented by the sperm concentration, the progressive motility, the sperm normal morphology and the semen volume and leukocytes count were studied. Results: the results of our study showed found a significant positive correlation between abstinence period with sperm concentration (r=0.24,p=0.015) while the results were revealed nonsignificant negative correlation between abstinence period with progressive motility and normal sperm morphology.